FACULTY CHOICE: ASPECTS THAT INFLUENCE YOUNG PEOPLE - Elena ȘESTAC (Association of Social and Educational Innovation, 2020)
Every year, thousands of young people are forced to choose a faculty, which is expected to develop professionally, intellectually and personally. Unfortunately, this election is not given the necessary importance, because it is perceived as a simple decision, without complications and without taking into account the repercussions that may exist in the future. The misinformation, the creation of the imaginary and the confusion they may face when choosing a career are examples of the problems that young people face. The present study aims to identify whether family, economic and aptitude aspects have occurred, so that the young student has chosen his career and to what extent it has influenced. Developed by qualitative methodology, this research aims to provide information on career choice. The research was carried out in a student dormitory questioning different students from various faculties. The results showed that the family aspect had a great influence on the participants, being placed on the first place of the studied aspects, and from an economic point of view, an influence was also observed in the choice of career, the aptitude did not have a great relevance in the results obtained